The free and cued selective reminding test: Validation for mild cognitive impairment and Alzheimer's disease - Lemos, Raquel; Simões, Mário R.; Santiago, Beatriz; Santana, Isabel (Journal of neuropsychology, 2015)
The International Working Group on Alzheimer's disease (AD) suggested the free and cued selective reminding test (FCSRT) to assess memory, as it showed high sensitivity and specificity in the differentiation of AD from healthy controls and other dementias. The FCSRT involves the use of selective reminding with semantic cueing in memory assessment. This study aims to validate the FCSRT for mild cognitive impairment (MCI) and AD through the analysis of the diagnostic accuracy and the suggestion of cut‐off scores. Patients were classified into two groups according to standard criteria: MCI (n = 100) and AD (n = 70). A matched control group (n = 101) of cognitively healthy subjects was included. The reliability and the validity of the FCSRT were analysed on the immediate (IR) and delayed (DR) recalls. The Cronbach's alpha was 0.915 for the IR and 0.879 for the DR. The total recall measures revealed good areas under the curve for MCI (IR: .818; DR: .828) and excellent for AD (IR: .987; DR: .991). Furthermore, the MCI group was subdivided with respect to a non‐similar/similar AD pattern of impairment, with almost half of the subjects showing an AD‐like decline. This analysis represents a novel contribution regarding the properties of the FCSRT in illustrating the heterogeneity of MCI at baseline. The FCSRT has proved to be a very useful tool in the characterization of the memory impairment of the AD spectrum.